Audit Sistem Informasi Penjualan Tunai dengan Pendekatan Resiko dan Pengawasan: Study Kasus pada PT. PKJ - Iwan Kurniawan Widjaya (Bina Nusantara University, 2014)
This research was conducted based on the evaluation about the performance of Sales information system in current system in PT PKJ. General control and application control had contributed in reducing any risk that migh occur in daily operations. Some recommendations had been submitted to the management in order to prevent any fraud or leak in any financial control. To improve the security and control in every process in sales and operational, system should have a proper control in input and output. Standarizations must be implemented in every step in applications to reduce the treats and vulnerabilities. This research can be used as a model for small medium company to grow better with proper control using optimalization of Information System and Technology in every aspect in the management.